Chromosome homogeneity in populations of Triatoma brasiliensis Neiva 1911 (Hemiptera - Reduviidae - Triatominae) Homogeneidade cromossômica em populações de Triatoma brasiliensis Neiva 1911 (Hemiptera - Reduviidae - Triatominae) - Francisco Panzera; Ruben Pérez; Paula Nicolini; Sonia Hornos; Jane Costa; Érika Borges; Liléia Diotaiuti; Christopher J. Schofield (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2000)
Triatoma brasiliensis is the most important vector of Chagas disease in the semiarid zone of the Northeast of Brazil. Several authors have reported the occurrence of four chromatic patterns with morphological, ecological, and genetic differences. In order to determine the existence of cytogenetic differentiation between these chromatic forms, we analyzed their karyotypes and the chromosome behavior during the male meiotic process. Triatoma brasiliensis shows distinct and specific chromosome characteristics, which differ from those observed in all other triatomine species. However, no cytogenetic differences were observed between the four chromatic forms of T. brasiliensis. The lack of chromosome differentiation among them could indicate that the populations of this species are in a process of differentiation that does not involve their chromosomal organization. Vários autores têm reportado a ocorrência de quatro padrões cromáticos e diferentes padrões morfológicos, genéticos e ecológicos de Triatoma brasiliensis no semi-árido nordestino do Brasil, região onde é o mais importante vetor da doença de Chagas. Para verificar diferenças citogenéticas nessas populações, foram analisados seus cariótipos e o comportamento cromossomial durante o processo meiótico em exemplares machos. Observou-se que o T. brasiliensis mostra características cromossômicas distintas e específicas entre as quatro populações, diferindo daquelas observadas em outras espécies de triatomíneos. No entanto, diferenças citogenéticas não foram observadas entre as quatro populações de T. brasiliensis, o que poderia indicar que as referidas populações ainda se encontram em uma etapa inicial do processo de diferenciação, ainda não envolvendo a organização cromossomial.